HIGH-STRENGTH ADMIXTURE FOR MORTAR OR CONCRETE - NAKAJIMA YUTAKA (2008)
PROBLEM TO BE SOLVED: To provide a high-strength admixture drastically increasing dispersibility of fine silica fume that strongly affects strengthening of mortar or concrete and sufficiently imparting high strength development to mortar or concrete with a low water content without reducing its flow property. SOLUTION: The high-strength admixture for mortar or concrete comprises 100 pts.mass silica fume and 100-600 pts.mass water-insoluble inorganic powder having specific gravity of 2.2-2.7 and substantially no hydration reactivity. Preferably, the high-strength admixture for mortar or concrete comprises silica stone powder as the water-insoluble inorganic powder. COPYRIGHT: (C)2008,JPO&INPIT